The tragedy of empire : from Constantine to the destruction of Roman Italy - Kulikowski, Michael (Harvard University Press, 2020)
Michael Kulikowski traces two hundred years of Roman history during which the Empire became ungovernable and succumbed to turbulence and change. A sweeping political narrative, The Tragedy of Empire tells the story of the Western Roman Empire's downfall, even as the Eastern Empire remained politically strong and culturally vibrant.